Pengembangan Pengelolaan Bank Sampah IKHLAS Perumahan Putri Tujuh II Kelurahan Sidomulyo Barat Kecamatan Tuahmadani Kota Pekanbaru - Joleha, Joleha; Hermita, Neni; Elianora, Elianora; Misriani, Merley; Yusnita, Yusnita; Fitri, Kurniawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Ikhlas Waste Bank is a newly established waste bank in 2023, located in Perumahan Putri Tujuh II, Sidomulyo Barat Village, Pekanbaru City. This waste bank currently has a relatively small number of customers, comprising only about 24% of the households. Additionally, the activities at the waste bank are still in the early stages of sorting waste. Therefore, the development of the waste bank is expected to improve waste management, both in terms of increasing the number of customers and expanding the range of activities. The method for this initiative involves motivating and educating residents through outreach and socialization. The material includes encouraging residents to raise awareness about reducing waste at landfills (TPA) and turning waste into money by depositing it at the waste bank. Furthermore, training is provided on creative activities to utilize waste through 3R (Reduce, Reuse, Recycle) practices. The 3R waste utilization training is very popular among residents, as it provides new skills and knowledge and offers economic benefits. Various recycled products are made from waste, such as wallets, bags, laptop cases, tumbler covers, and more. These products can be used personally or marketed online. Thus, the waste bank not only collects waste from the community but also transforms it into useful items.